2021
DOI: 10.3390/ijerph19010055
|View full text |Cite
|
Sign up to set email alerts
|

The Diet of Children Attending a Holiday Programme in the UK: Adherence to UK Food-Based Dietary Guidelines and School Food Standards

Abstract: Child poverty rates are rising, particularly in London, putting more children at risk of experiencing food insecurity. Holiday programmes in the UK provide children who receive free schools meals during term time with access to free/low-cost holiday clubs offering nutritious food and enriching activities during the school holidays. This study aimed to investigate whether children’s dietary intake was more adherent to the UK Eatwell Guide throughout the day and meets School Food Standards (SFS) for the lunchtim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To alleviate these issues, holiday clubs, which extend beyond solely providing access to food, have formed over recent years [ 5 , 6 ] and research has demonstrated significant social and health benefits of attendance, both for school-aged children and their wider families [ 7 , 8 , 9 ]; with food insecure households benefitting most from holiday provision [ 10 ]. Importantly, food diaries have demonstrated that attendance at holiday clubs improves dietary intake, with a higher consumption of core-foods on attendance days [ 7 ], and better adherence to UK dietary guidelines [ 11 , 12 ]. Moreover, both children and parents have reported numerous positive benefits of attending holiday clubs, including improved physical, social, and emotional wellbeing, and dietary intake [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate these issues, holiday clubs, which extend beyond solely providing access to food, have formed over recent years [ 5 , 6 ] and research has demonstrated significant social and health benefits of attendance, both for school-aged children and their wider families [ 7 , 8 , 9 ]; with food insecure households benefitting most from holiday provision [ 10 ]. Importantly, food diaries have demonstrated that attendance at holiday clubs improves dietary intake, with a higher consumption of core-foods on attendance days [ 7 ], and better adherence to UK dietary guidelines [ 11 , 12 ]. Moreover, both children and parents have reported numerous positive benefits of attending holiday clubs, including improved physical, social, and emotional wellbeing, and dietary intake [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that the food and nutrition Aims and Standards were often not met, there needs to be greater uptake and provision of the training provided by the Co-ordinators and greater support given to the Providers to ensure that nutrition education Aims are attained in any future HAF Programme provision. Creating training resources for Providers that facilitates the delivery of nutrition education to children and parents would be beneficial as it has been reported that when children have attended the HAF Programme, the quality of their diet improved in comparison to when they did not attend ( 29 ). Our findings further support prior recommendations to provide examples of best practice on experiential learning, resources that can be used at home, and use learning from the family food education sessions to understand how a range of families can be engaged positively ( 14 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a condition for the funding, holiday clubs have to provide at least one meal a day that meets the School Food Standards (SFS), which consist of food-based requirements to ensure that the food and drinks served at state-funded schools foster health and encourage positive eating habits [19]. To date, the adherence to SFS by HAF providers has not been evaluated [20,21]. Furthermore, to the authors' knowledge, there is a lack of studies investigating the nutritional quality of the food provided.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to the authors' knowledge, there is a lack of studies investigating the nutritional quality of the food provided. Previous research has focused on the food consumed at pre-HAF holiday clubs which showed promising, yet mixed, results [20,[22][23][24]. For example, Crilley et al (2022) found that participants followed a healthier diet overall and that what they eat was more adherent to SFS when they attended the holiday club compared to when they did not attend [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation